Estudio de prefactibilidad para la implementación de una planta productora de langostino blanco congelado (Penaeus vannamei) bajo el método de ultracongelación para su exportación a España - Zavala Mestanza, Jesús David (2015)
For this project we have decided to work with a product for export because of its high nutritional value and because their valuation - quality is highly appreciated by European and American consumer. Among the main consumers of Peruvian seafood products, USA accounts for 52%, EU 43% and Asia 5%. Also, the Spanish market was chosen as frozen shrimp is a very popular because of its texture, taste and price product. For specific demand was segmented geographically the market focused on the Spanish market and its autonomous community of greater participation in the demand for frozen crustaceans, Catalunia, then investigated how was segmented demand for this product in the market of Catalunia, knowing that retired adults, adult couples without children and adult couples with grown children are consuming the most shrimp segment, it is estimated that 2023 will be supplied to the market of Catalonia with boxes of finished product 39.489 (789 769 kg of shrimp). As for the location the proximity of raw materials as the most important factor because this variable will influence the 4-axis value consumer who appreciates color, taste, smell and texture, why the project will be considered in district of Tumbes, Tumbes province since it is the nearest to shrimp farming area. Plant size will be limited by market size factor, while the lower value is the point size of balance capacity market size (3,291 units monthly finished product) because choosing the equilibrium point will be chosen would produce only to avoid losses and produce the amount of size - technology (3,375 units per month) lead storage overruns, the chosen plant size will be 3,291 units per month. As for the technology to be used in this project will be automated, which will provide more productive, economic performance and maintaining product quality to perform. Finally, the duration of this project has been estimated to approximately 13 months and the pre-feasibility study for the installation of the plant shows that the amount of the estimated investment amounts to S /. 3,000,748 obtaining a financial TIR of 74%.